Cassava in Caicedonia: Present status - Toro M., J.C.; García P., S. (International Center for Tropical Agriculture, 1979)
The present situation of cassava cultivation in Caicedonia (Colombia) is studied after 8 yr cooperation between the Nat. Federation of Coffee Growers and CIAT. From an iitial 60 ha and 8 farmers in 1971, the project had developed more than 1300 ha (90 farmers) by the end of 1978. Yields have declined considerably as a result of pests, diseases and continuous cropping without fertilizer. The role of the extension agent in recommending effective cultural practices is emphasized. (CIAT)